1983
DOI: 10.1097/00000658-198311000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Determining Criteria for Shunt Placement During Carotid Endarterectomy

Abstract: EEG monitoring and carotid back pressure were performed on 100 patients undergoing elective carotid endarterectomy. Shunts were inserted selectively in those patients who showed change in EEG after a trial period of carotid clamping (15%). No patient in the series awoke with a neurologic deficit. Back pressures were significantly lower in the shunted group and these pressures roughly correlated with EEG changes. Only one patient with a back pressure of greater than 40 mmHg had EEG changes and this patient had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 15 publications
0
25
0
1
Order By: Relevance
“…Several authorities have correlated EEG monitoring and stump pressure measurement in patients undergoing general anesthesia and in awake patients to determine the reliability of these methods in detecting cerebral ischemia and selecting shunting. 9,15,16,[35][36][37][38] Selective shunting according to EEG changes is associated with a need for shunting in 15% to 18% of patients. 9, 15 Calligaro and Dougherty 16 reported the correlation of carotid artery stump pressure and neurologic changes during 474 CEAs performed in awake patients and indicated if CEA had been performed under general anesthesia, shunts would have been placed in 29% of patients if a stump pressure of Ͻ50 mm Hg systolic had been used as the threshold for shunting, and about 15% would have been shunted had a stump pressure of Ͻ40 mm Hg systolic been used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authorities have correlated EEG monitoring and stump pressure measurement in patients undergoing general anesthesia and in awake patients to determine the reliability of these methods in detecting cerebral ischemia and selecting shunting. 9,15,16,[35][36][37][38] Selective shunting according to EEG changes is associated with a need for shunting in 15% to 18% of patients. 9, 15 Calligaro and Dougherty 16 reported the correlation of carotid artery stump pressure and neurologic changes during 474 CEAs performed in awake patients and indicated if CEA had been performed under general anesthesia, shunts would have been placed in 29% of patients if a stump pressure of Ͻ50 mm Hg systolic had been used as the threshold for shunting, and about 15% would have been shunted had a stump pressure of Ͻ40 mm Hg systolic been used.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11]14,16,17 Some have suggested a systolic stump pressure of Ͻ50 mm Hg and Ͻ40 mm Hg, and others selected a mean stump pressure of 50, 45, 40, or 25 mm Hg. A few randomized trials have compared routine vs selective shunting during CEA, 8,13,29 but none were based on stump pressure.…”
mentioning
confidence: 99%
“…Studies have shown several criteria to determine the need for carotid shunt placement during surgery, which include SP, EEG, TCD, SSEP, and NIRS. [12][13][14][15][16][17][18][19][20][21][22][23] In our cohort, shunts would have been placed in 12.8% of patients using the SPs 40 mm Hg criteria; however, less than half of these (5.8%) actually underwent shunting based on the WUT criteria. Moreover, 20% of patients (4/20) with a normal SPs >40 mm Hg criteria (false negative) required shunting due to neurological change (positive WUT).…”
Section: Discussionmentioning
confidence: 99%
“…No single method has shown to offer better surgical outcomes to date. [20][21][22] The systolic SP (SPs) criteria is generally used for selective shunting insertion under GA 15,16 when SP <50 mm Hg. This cutoff value, however, includes false-positive and false-negative rates.…”
Section: Introductionmentioning
confidence: 99%
“…Some never use shunts periprocedurally. [6][7][8][9][10][11][12][13][14] So far, no evidence for routine or selective shunting has been presented.…”
Section: Introductionmentioning
confidence: 99%